Społeczne budownictwo czynszowe jako usługa w ogólnym interesie gospodarczym - Bujny, Jędrzej; Maśliński, Mikołaj (Studia Prawa Publicznego, 2019)
Social rental housing is one of the possible instruments which are applied to ensure the satisfaction of housing needs. However, public funds which are transferred to entities that operate within this area should be usually classiﬁed as State aid. The analysis presented in this paper concerns the following question: is it possible to consider the operation of a social rental housing program as services of general economic interest. This question seems to be a topical issue because of a new legislative initiative aiming at establishing a governmental housing program that was implemented by the Act of 10 September 2015 which amended the Act on certain forms of supporting housing construction. The aforementioned program stipulates the legal frames for refundable and preferential ﬁnancing that may be granted to speciﬁc entities in order to realise investments in social rental housing. The governmental housing program complements earlier local housing policies in force. What is signiﬁcant is that the Polish legislator decided to qualify support granted as services of general economic interest, as referred to in Commission Decision 2012/21/UE of 20 December 2011 on the Application of Article 106(2) of the Treaty on the Functioning of the European Union to State aid in the form of public service compensation granted to certain undertakings entrusted with the operation of services of general economic interest. Applying Commission Decision 2012/21/UE to this situation raises some doubts as to the lack of clarity of a term “social housing”. Due to a certain controversy over the abovementioned issue, the authors have attempted to examine whether the application of preferential provisions of Commission Decision 2012/21/UE to the social housing program is in accordance with the relevant provisions of EU competition rules.